Faktor psikologis pemilik UMKM knalpot terhadap pengambilan keputusan keuangan di Kabupaten Purbalingga - Isnaeni Rokhayati; Mayla Surveyandini; Heru Cahyo (Journal of Management and Digital Business, 2025)
The research aims to determine the influence of psychological factors on the financial decisions of micro, small, and medium enterprise owners. The population consisted of 90 muffler MSME owners in Purbalingga Regency, with 48 respondents selected as the sample. Data analysis used multiple linear regression. The analysis shows that financial knowledge, financial attitudes, and financial planning significantly influence the financial decision-making of muffler MSMEs in Purbalingga Regency. These findings suggest that psychological factors, such as financial knowledge, financial attitudes, and financial planning, possessed by micro, small, and medium enterprise owners can influence their financial decision-making in their businesses. Based on the study’s results, it is clear that a business owner must always pay attention to the psychological factors of financial knowledge, financial attitudes, and financial planning in every consideration of financial decisions in their business activities.